Cellular immunity induced by the recombinant Plasmodium falciparum malaria vaccine, RTS,S/AS02, in semi-immune adults in The Gambia. - Pinder, M; Reece, W; Plebanski, M; Akinwunmi, P; Flanagan, K; Lee, E; Doherty, T; Milligan, P; Jaye, A; Tornieporth, N; Ballou, R; McAdam, K; et al. (2004)
Vaccination of malaria-naive humans with recombinant RTS,S/AS02, which includes the C-terminus of the circumsporozoite protein (CS), has been shown to induce strong T cell responses to both the whole protein antigen and to peptides from CS. Here we show that strong T cell responses were also observed in a semi-immune population in The Gambia, West Africa. In a Phase I study, 20 adult male volunteers, lifelong residents in a malaria-endemic region, were given three doses of RTS,S/AS02 at 0, 1 and 6 months. Responses to RTS,S, hepatitis B surface antigen and peptides from CS were tested using lymphocyte proliferation, interferon (IFN)-gamma production in microcultures, and IFN-gamma ex vivo and cultured ELISPOT, before and after vaccination. Cytotoxic responses were tested only after vaccination and none were detected. Before vaccination, the majority of the volunteers (15/20) had detectable responses in at least one of the tests. After vaccination, responses increased in all assays except cytotoxicity. The increase was most marked for proliferation; all donors responded to RTS,S after the third dose and all except one donor responded to at least one peptide after the second or third dose. There was a lack of close association of peptide responses detected by the different assays, although in microcultures IFN-gamma responses were found only when proliferative responses were high, and responses by cultured ELISPOT and proliferation were found together more frequently after vaccination. We have therefore identified several peptide-specific T cell responses induced by RTS,S/AS02 which provides a mechanism to investigate potentially protective immune responses in the field.